In-Home Passive Sensor Data Collection and Its Implications for Social Media Research: Perspectives of Community Women in Rural South Africa. (February 2020) - van Heerden, Alastair; Wassenaar, Doug; Essack, Zaynab; Vilakazi, Khanya; Kohrt, Brandon A.
There has been a recent increase in debates on the ethics of social media research, passive sensor data collection, and big data analytics. However, little evidence exists to describe how people experience and understand these applications of technology. This study aimed to passively collect data from mobile phone sensors, lapel cameras, and Bluetooth beacons to assess people's understanding and acceptance of these technologies. Seven households were purposefully sampled and data collected for 10 days. The study generated 48 hr of audio data and 30, 000 images. After participant review, the data were destroyed and in-depth interviews conducted. Participants found the data collected acceptable and reported willingness to participate in similar studies. Key risks included that the camera could capture nudity and sex acts, but family review of footage before sharing helped reduce concerns. The Emanuel et al. ethics framework was found to accommodate the concerns and perspectives of study participants.